What Constitutes Poor Teaching? A Preliminary Inquiry Into the Misbehaviors of Not-So-Good Instructors. (October 2017) - Busler, Jessica; Kirk, Claire; Keeley, Jared; Buskist, William
Across three phases, we investigated college students' perceptions of poor college teaching to develop a typology of poor teaching behaviors. In Phase 1, students generated a list of qualities representative of poor teaching. In Phase 2, another group of students assigned behavioral correspondents to these qualities, resulting in a list of 15 poor teaching qualities and their attendant misbehaviors. Finally, in Phase 3, yet another group of students generated a "top 5" list of qualities and behaviors that their most ineffective teachers have exhibited. Across participants in Phase 3, the top 5 list included, in order, being disrespectful, offering unrepresentative and unfair student learning assessments, having unrealistic expectations for student learning, being less than knowledgeable on course content, and having poor communication skills. These findings provide practical guidance on which particular behaviors teachers should avoid adopting in their instructional repertoires.